Comparison of Proteomics Profiles of Campylobacter jejuni Strain Bf under Microaerobic and Aerobic Conditions - Rodrigues, Ramila C.; Haddad, Nabila; Chevret, Didier; Cappelier, Jean-Michel; Tresse, Odile (Frontiers in Microbiology, 2016)
Campylobacter jejuni accounts for one of the leading causes of foodborne bacterial enteritis in humans. Despite being considered an obligate microaerobic microorganism, C. jejuni is regularly exposed to oxidative stress. However, its adaptive strategies to survive the atmospheric oxygen level during transmission to humans remain unclear. Recently, the atypical clinical C. jejuni Bf strain was shown by its unexpected ability to grow under ambient atmosphere. Here, we aimed to understand better the biological mechanisms underlying its atypical aerotolerance trait using two-dimensional protein electrophoresis, gene expression and enzymatic activities. Forty-seven proteins were identified with a significantly different abundance between cultivation under microaerobic and aerobic conditions. The over-expressed proteins in aerobiosis belonged mainly to the oxidative stress response, modulation of the main enzymes of the tricarboxylic acid cycle, iron uptake and regulation and amino acid uptake when compared to microaerobic conditions. The higher abundance of proteins related to oxidative stress was correlated to dramatically higher transcript levels of the corresponding encoding genes in aerobic conditions compared to microaerobic conditions. In addition, a higher catalase-equivalent activity in strain Bf was observed. Despite the restricted catabolic capacities of C. jejuni, this study reveals that strain Bf is equipped to withstand oxidative stress. This ability could contribute to emergence and persistence of particular strains of C. jejuni throughout food processing or macrophage attack during human infection.